2014
DOI: 10.1002/2013gc005034
|View full text |Cite
|
Sign up to set email alerts
|

Magnetotaxis and acquisition of detrital remanent magnetization by magnetotactic bacteria in natural sediment: First experimental results and theory

Abstract: [1] The widespread occurrence of magnetotactic bacteria (MTB) in several types of marine and freshwater sediment, and the role of fossil magnetosomes (magnetofossils) as main remanent magnetization carriers therein, has important paleomagnetic and paleoenvironmental implications. Despite numerous studies on MTB biology and on magnetofossil preservation in geological records, no detailed information is yet available on how magnetotaxis (i.e., the ability to navigate along magnetic field lines) is performed in s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
72
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 46 publications
(76 citation statements)
references
References 96 publications
(155 reference statements)
4
72
0
Order By: Relevance
“…The finding that the total number of MTB increased over time suggests that the changes in the horizontal distribution do not stem from migration but rather are due to changes in cell division (growth) and death rates, which then trended toward relatively equal numbers at the latter stages of the experiment in both aquaria. This is consistent with the observations of Mao et al (21), who found that MTB move via a slightly biased random walk in the external magnetic field in the sediment. While the swimming velocity of MTB cocci in water can reach 112 m/s (25), their swimming velocity in sediment is unknown.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…The finding that the total number of MTB increased over time suggests that the changes in the horizontal distribution do not stem from migration but rather are due to changes in cell division (growth) and death rates, which then trended toward relatively equal numbers at the latter stages of the experiment in both aquaria. This is consistent with the observations of Mao et al (21), who found that MTB move via a slightly biased random walk in the external magnetic field in the sediment. While the swimming velocity of MTB cocci in water can reach 112 m/s (25), their swimming velocity in sediment is unknown.…”
Section: Discussionsupporting
confidence: 93%
“…After aquarium A was rotated 180°on day 44, MTB rods did not flourish in the "new" northern part of the aquarium or die off toward the south. Because the sediment was mixed into the aquaria in the magnetic field, and because MTB swimming velocities are higher in water than in sediment (21), the fact that MTB rods were concentrated in the north could indicate that pouring the sediment into the aquaria in the ambient field might have biased the initial results. On the other hand, the finding that MTB rods died off in aquarium A and not in aquarium B, whereas MTB cocci and MTB spirilla were less affected by the rotation, suggests that the change in the magnetic environment influenced the MTB rod community.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This result is significant for three reasons. First, prior associations of BS-BM and BH-BI with magnetofossils remains speculative because numerical inversion of magnetization curves through which they were originally conceived 19 and continuously presumed 16,[48][49][50][51] has non-unique solutions. In addition, the coercivity distributions (characterized by skewness, median coercivity and dispersion factor) of diverse MTB types found in nature are poorly constrained.…”
Section: Resultsmentioning
confidence: 99%
“…Third, the skewed coercivity distributions that characterize uncultivated MTB point to the importance of modelling them as such, rather than symmetric distributions, so as to avoid the addition of coercivity distribution components that are not physically meaningful when quantifying the amount of magnetofossils. Both approaches are widely used 19,[50][51][52][53] .…”
Section: Resultsmentioning
confidence: 99%